Begging in light of the Syrian crisis (Damascus University Journal of arts and humanities sciences, 2022)
Begging is a very complex problem, and society must find appropriate solutions that help to reduce its spread, rehabilitate these children and adapt them to the behavioral patterns that society wants to rid themselves of those behavioral patterns that they are accustomed to and pose a danger to society and its citizens.By the spread of begging in the streets of Damascus in the light of the crisis and using children to beg on the part of the people who do begging, the problem of the research is the following question: What is begging?So the importance of research stems from the use of research and the beneficiaries: The researcher herself is learning why children are used to begging, Workers in humanitarian and social organizations in identifying possible solutions to begging, and Legal bodies to enact appropriate regulations and legislation for begging[1]. [1]– the linguistic concept of begging:The origin of the word begging in the language goes back to: Seoul, meaning abdominal relaxation, (IbnManzour, DT: 350). Begging is called the practice of redemption and redemption for money or food, beggar may be made to have physical impairment, bad situation or exploitation of children to this end, and classified as negative phenomena.
Keywords: begging; the crisis; Syria